THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN MEDIATING THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE (Case Study at PT Bank Negara Indonesia (Persero) Tbk. Kupang Branch Office) - Nyoman Mariadi; Putu Indah Rahmawati; Ni Luh Wayan Sayang Telagawathi; Komang Krisna Heryanda; I Nengah Suarmanayasa (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of organizational culture and organizational commitment on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable at PT Bank Negara Indonesia (Persero) Tbk Kupang Branch Office. This study uses a quantitative method with an associative approach. The sample was determined by a non-probability sampling technique on BNI Kupang Branch employees. Data collection was carried out by distributing questionnaires to 118 respondents. Data analysis used Partial Least Square (PLS) with the help of SmartPLS 4.0 software. The results of the study indicate that: (1) Organizational culture has a positive and significant effect on employee performance; (2) Organizational commitment does not have a significant effect on employee performance; (3) Organizational culture has a positive and significant effect on OCB; (4) Organizational commitment has a positive and significant effect on OCB; (5) OCB has a positive and significant effect on employee performance; (6) OCB partially mediates the effect of organizational culture on employee performance; and (7) OCB fully mediates the effect of organizational commitment on employee performance. Consistent with previous research, these results confirm that organizational culture is a crucial factor in enhancing employee OCB. Practically, these findings provide implications for BNI Kupang Branch that employee performance improvements can be achieved by strengthening organizational culture, organizational commitment, and consistently encouraging OCB behavior.